Implementation of a Web-Based Information Management System for Masjid Al-Mukhlisin - Muslim; Santosa, Firman; Amelia Chandra, Detri; Oktafanda, Ego; Zainab, Siti (Journal of ICT Applications System, 2024)
Al-Mukhlisin Mosque is a mosque located in Rantau Panjang Village. The mosque has a function as a place of worship, therefore it can be found various religious activities such as paying Zakat Mal, Zakat Fitrah, Infak, Sacrifice, Islamic Holiday Celebration, cult (Seven Minute Lecture) in Ramadan, and so on and so forth. At this time the problem that exists in Al-Mukhlisin Mosque is that data recording is still using a manual method written in books and then recorded and making reports from the data that has been collected. And the mosque has difficulty in recapitulation and searching for data in the mosque if needed at any time because it uses a manual process. The design of the mosque management information system at Al-Mukhlisin Mosque aims to make it easier to manage and search for data and data recapitulation. This mosque information system is web-based using PHP program tools, databases, XAMPP, MYSQL.